Risk of Developing Post-traumatic Stress Disorder in Severe COVID-19 Survivors, Their Families and Frontline Healthcare Workers: What Should Mental Health Specialists Prepare For? - Sekowski, Marcin; Gambin, Małgorzata; Hansen, Karolina; Holas, Paweł; Hyniewska, Sylwia; Wyszomirska, Julia; Pluta, Agnieszka; Sobańska, Marta; Łojek, Emilia (Frontiers in Psychiatry, 2021)
Given the high coronavirus disease 2019 (COVID-19) mortality, this disease may be a life-threatening event, especially for individuals at high risk of complications. Therefore, in the article we try to answer two questions that are relevant to public mental health: Can we define groups who are at higher risk of developing pandemic-related PTSD? How can health specialists prepare for it? Given the results of previous research on PTSD in epidemic (e.g. SARS) survivors, we suggest that mental health professionals in countries touched by the pandemic should prepare for an increase in the PTSD prevalence, specifically in: individuals who have had severe COVID-19; family members of these patients and of patients who have died; and frontline healthcare workers witnessing COVID-19 patients' sudden deaths, or numerous life-threatening situations. We postulate that these groups at risk should be routinely screened for PTSD in primary medical and pediatric care. Mental health services should prepare for providing therapeutic interventions for individuals with PTSD in the vulnerable groups, and support to their families, especially children.